Design features of brake pads of agricultural machinery that can affect their efficiency under different operating conditions (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The brake pad is one of the key components of the safety of both passengers and cargo. It plays a crucial role in the management of motor vehicles and machine equipment, and its design features determine the braking efficiency, durability, environmental friendliness and safety of the vehicle. The tribological characteristics of disc brakes largely depend on the design and materials from which the brake discs and pads are made and the friction coefficient that occurs between them. The latter significantly depends on the temperature and condition of the friction surface. With excessive heating (for example, during intensive braking), the effect of burnout of the friction material occurs, which leads to a loss of the friction coefficient and a decrease in braking efficiency. The work theoretically substantiates the dependence of braking on the temperature conditions of operation of the brake system of motor vehicles. The efficiency of the improved brake pad 2TP-114 Tp108 R3 under different temperature conditions was investigated and its performance was compared with three other brake pad samples used in Ukrainian vehicles.The results of tests conducted on the TecSA TTR2600 inertial dynamometer of LLC "BCZ "Tribo" according to ISO 26866:2009 showed that the proposed brake pad sample successfully passed the test and, in comparison with the other three samples, showed good results (in tests for braking efficiency with changes in temperature and speed, it showed a stable 2nd place), inferior in individual indicators only to sample "2". Moreover, in the running-in test, it required the least number of braking operations to reach a stable braking torque, which indicates its advantages when lapping new pads to the disc when replacing them, which can be used in vehicle service.
Keywords: wear braking; friction coefficient; lapping; temperature regimes; tribological characteristics; friction materials